2013
DOI: 10.1016/j.geoderma.2013.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Biological and chemical factors controlling the patchy distribution of soil water repellency among plant species in a Mediterranean semiarid forest

Abstract: Natural soil water repellency is a property that has already been observed in forest soils and is characterized by its patchydistribution. Ihere are many factors involved in its development. In this work, we have studied a large numberof chemical and biological factors underthe influence of differentplantspecies (Pinus halepensis, Quercus rotundifolia, Cistus albidus and Rosmarinus officinalis) to leam which has the greatest responsibility for its presence and persistence in the top-soillayer. We obselVed stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 69 publications
9
56
1
Order By: Relevance
“…This contribution is a continuation of previous research (Lozano et al, 2013), where we concluded that the quality of SOM, in specific a lipid fraction, could be the main factor involved in SWR. However, in the case of forested land with Pinus, it was also postulated that soil microbiology could be another major factor, but this was not investigated.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…This contribution is a continuation of previous research (Lozano et al, 2013), where we concluded that the quality of SOM, in specific a lipid fraction, could be the main factor involved in SWR. However, in the case of forested land with Pinus, it was also postulated that soil microbiology could be another major factor, but this was not investigated.…”
Section: Introductionsupporting
confidence: 79%
“…Previous research has shown that water repellent patches of soil differ from adjacent wettable soils in pH, moisture, SOM quality and quantity, and microbial biomass (Doerr et al, 2000), even beneath the same plant species (Lozano et al, 2013). When soil microorganisms decompose SOM, hydrophilic compounds are more readily degraded, potentially resulting in an accumulation of hydrophobic compounds over time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been very frequently reported in literature over the last years that coniferous forest litter causes the strongest levels of SWR (e.g. de Blas et al, 2013;Flores-Mangual et al, 2013;Lozano et al, 2013), most probably due to high content of hydrophobic resins, terpens, and waxes.…”
Section: Water Repellency Effects At Scale Of Minidisc Infiltrometer mentioning
confidence: 98%